Factors Influencing Entrepreneurial Interest With Moderating Environmental Support Variables - Sirine, Hani; Fira Indriana , Anindya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The growth of entrepreneurship in a country is an important factor in spurring the economy and creating jobs. However, entrepreneurial interest can be influenced by various factors, including financial literacy, digital literacy, adversity intelligence, and entrepreneurial spirit. However, it is unclear how these factors interact and influence an individual's entrepreneurial interest, especially considering the potential moderation of environmental support. This research aims to investigate the relationship between financial literacy, digital literacy, adversity intelligence, and entrepreneurial spirit with entrepreneurial interest. In addition, this research also aims to evaluate whether environmental support moderates the relationship between these factors and entrepreneurial interest. Data was collected through a survey of 500 respondents representing a variety of backgrounds and experiences. Statistical analysis was used to evaluate the relationships between these variables and examine the potential moderation of environmental support. The research results show that financial literacy, digital literacy, and entrepreneurial spirit have a significant influence on entrepreneurial interest with path coefficients of 0.104, 0.080, and 0.101, respectively. However, no significant relationship was found between adversity intelligence and entrepreneurial interest. In addition, there is no evidence to support the moderation of environmental support in the relationship between these factors and entrepreneurial interest